Torregarcía, Purpura y Agua (BAR Publishing, 2023)
Along the coast of the southeast of the Iberian Peninsula, there are numerous remains linked to the manufacture of purple dyes. This study focuses on the site of Torregarcía (Almería, Spain), located in the Cabo de Gata-Níjar Natural Park, a protected coastal area of particular ecological interest. Torregarcía was initially excavated during 1980s and was identified as a Roman salting factory where the complementary activity of dyeing was also practised. Despite its importance, it has gone unnoticed in the historiography of the last three decades and has never been the subject of dedicated scientific publication. The investigations presented in this book have been carried out using non-invasive prospecting techniques, such as ground-penetrating radar (GPR), and have revealed the importance of the exploitation of purple dye as the main site activity. More complex installations associated with the excavated structures and a large shell pit are also described. Alongside these, other buildings and shells have also been documented along the coastline of this site. All of this forms what we call the "purple landscape" in the southeast of the peninsular coast, which allows the Natural Park to show archaeological heritage beyond any excavations carried out to date.